2012
DOI: 10.1111/btp.12007
|View full text |Cite
|
Sign up to set email alerts
|

Population Composition and Ectoparasite Prevalence on Bats (Sturnira ludovici; Phyllostomidae) in Forest Fragments and Coffee Plantations of Central Veracruz, Mexico

Abstract: Studies comparing the abundance of frugivorous bats in shade‐coffee plantations and forest fragments report contradictory results, and have not taken into account the landscape context in which coffee plantations are immersed. Variables of population composition such as abundance, sex proportion, and reproductive condition, together with biological tags (i.e., bat fly prevalence), can provide information about spatiotemporal dynamics of habitats used by bats. In the central part of Veracruz, Mexico, we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The three REGUA sites, F10, and F4 are the only sampling sites where the bat species Artibeus lituratus and Desmodus rotundus and their respectively associated bat flies Paratrichobius longicrus and Strebla wiedemanni were collected; all other sites are missing one or more of these species. Bat species and bat fly species responses to habitat disturbance are highly species specific, and may not always be negative (Hiller et al, 2020;Pilosof et al, 2012;Saldaña-Vázquez et al, 2013). Anecdotally, site F4 had many large trees, suitable for roosts, compared to other patches of similar size.…”
Section: Island Biogeography Theory Applied To the Microbiomes Of Parasitesmentioning
confidence: 99%
“…The three REGUA sites, F10, and F4 are the only sampling sites where the bat species Artibeus lituratus and Desmodus rotundus and their respectively associated bat flies Paratrichobius longicrus and Strebla wiedemanni were collected; all other sites are missing one or more of these species. Bat species and bat fly species responses to habitat disturbance are highly species specific, and may not always be negative (Hiller et al, 2020;Pilosof et al, 2012;Saldaña-Vázquez et al, 2013). Anecdotally, site F4 had many large trees, suitable for roosts, compared to other patches of similar size.…”
Section: Island Biogeography Theory Applied To the Microbiomes Of Parasitesmentioning
confidence: 99%
“…Similar studies in Mexico with S. ludovici (before the study of Velazco & Patterson , also found no significant differences in the prevalence of ectoparasites in cloud forest fragments or coffee plantations; although in the first, a higher prevalence of ectoparasitism was recorded (Saldaña‐Vásquez et al . ).…”
Section: Discussionmentioning
confidence: 97%